PHYTOCHEMICAL SCREENING AND IN VITRO ANTIMICROBIAL ACTIVITY OF METHANOLIC ROOT EXTRACT OF Ampelocissus grantii (Baker) Blanch. (Vitaceae) - S. Y, MAIYAMA; H, DAHIRU; M. L, MOHAMMED; M. E, HALILU; OGUEJIOFOR, C. J, UGWAH; A, BABAGANA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
grantii is a medicinal plant widely used in traditional medicine for the treatment of many diseases including bacterial and fungal infections. This research was designed to conduct phytochemical screening and investigate the antimicrobial potential of methanolic extract of A. grantii root. The sample was collected, shade dried, ground into powder and extracted by maceration using 100 % methanol. The liquid extract was evaporated to dryness and subjected to phytochemical screening and antimicrobial test using various concentrations (200, 100, 50 and 25 mg/ml) to examine the susceptibility of clinical isolates of bacteria (Pseudomonas aeruginosa, Escherichia coli) and fungi (Aspergillus niger and Candida albicans) using standard procedures. Phytochemical screening revealed the presence of steroid/triterpenes, tannins, flavonoids, saponins and proteins. However, alkaloids were not detected. The result showed that the activity of the extract is concentration dependent, with the highest value of the zone of inhibition observed at 200 mm/ml for both antibacterial and antifungal tests. The antimicrobial activity may be due to the presence of these phytochemicals. Therefore, A. grantii can be used a precursor for new antimicrobial drug synthesis.